Effect of the Dominant Follicle Aspiration before or after Luteinizing Hormone Surge on the Corpus Luteum Formation in the Cow - MATSUI, Motozumi; HAYASHI, Ken-Go; ACOSTA, Tomas J.; MIYAMOTO, Akio; KIDA, Katsuya (Journal of Reproduction and Development, 2006)
Luteinizing hormone (LH) surge and follicle rupture act as trigger to start corpus luteum (CL) formation. Thus, we aimed to investigate whether a dominant follicle that has not been exposed to an LH surge can become a functional CL. For this purpose, follicular fluid from the dominant follicles (DF) of cows was aspirated before or after a GnRH-induced LH surge, and subsequent CL formation was observed. Holstein cows were divided into four groups as follows: Luteal phase, a DF was aspirated 7 days after GnRH injection; Pre-LH surge, a DF was aspirated 42 h after PGF2α injection during the mid luteal phase; Post-LH surge, a DF was aspirated 24 h after GnRH injection following PGF2α; and Intact follicle, ovulation was induced by GnRH injection after PGF2α. Observation of morphological changes in the aspirated follicle using color Doppler ultrasonography and blood sampling was performed on Days 0, 3, 6, and 9 (Day 0=follicle aspiration). CL formation following DF aspiration was observed only in the Post-LH surge group. In both the Luteal phase and Pre-LH surge groups, however, none of the cows showed local blood flow at the aspirated site or CL formation. Luteal blood flow area, CL volume, and plasma progesterone concentration in the Post-LH surge group were no different from those in the Intact follicle group. The present results clearly demonstrate that rather than follicle rupture, it is the LH surge that is essential for CL formation in cows.